Correlation between Women’s Attitudes and Abstain (Used/ Unused) Contraceptive Methods at Primary Health Care Centers in Baghdad City - Maha Khaled Rida1 , Hawraa Hussein Ghafel2 (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: family planning is a preventive service that allows married couples achieving their desirednumber of children and deciding the spacing of pregnancies according to their economic opportunities andpersonal wishes, and to ensure that the births are at appropriate intervals for the mother and child health.Objective: To find out the correlation between women attitudes and abstain and to find out the relationshipbetween demographic characteristics and obstetrical history.Methodology: A descriptive and analytic (cross sectional) study, was started at 16th September 2019 to16th September 2020, conducted at Primary Health Care Center in Baghdad City,Iraq. Non probability (apurposive sample) the study sample consist of (150) women that attending Primary Health Care Center inBaghdad City,Iraq.Results: indicates that there is significant relationship between women’s attitude and abstain of contraceptivemethods as presented by significant correlation at p-value= 0.038.Conclusions: there is significant relationship between women’s attitude and abstain of contraceptivemethods related to Iraqi social habits that make men compel women to become pregnant and have a lot ofchildren and there are other causes prevent women using contraceptive methods.Recommendation: Designing programs to educate couples about family planning and using of contraceptivebefore marriage, Empowering the role of nurse in family planning to educate the women about contraceptivemethods and how to use it and help them to choice the appropriate method, Activate the role of media inincrease awareness of families in the Iraqi society about disadvantages of unplanned pregnancies and donot using contraceptive methods on women well-being and the luxury of community, and further studies toidentifying the causes that make women do not use of contraceptive methods.